The impact of mobile devices on the in store shopping experience - Cavalinhos, Sílvia Rodrigues (2022)
Mobile devices have changed our daily lives and access to information. This phenomenon is continually changing the shopping experience, being an opportunity for retailers to influence customers' attitudes and behaviour. The main objective of this investigation was to provide an integrated model to analyse the effects of mobile devices use on the shopping experience in a store environment and, consequently, on customer satisfaction and their repatronage intention. The methodology of this thesis was based on a triangulation process consisting of two preliminary qualitative studies that contributed to the development of knowledge on the subject and the construction of the theoretical model. They also contributed to the interpretation of the results of the quantitative study in which the theoretical model is tested. Data collection was based on a questionnaire, and the final sample consisted of 301 participants. The proposed model was measured and tested using Confirmatory Factor Analysis and Structural Equation Models, respectively. This investigation dispels retailers' doubts about the positive effects of mobile devices and the scarce and scattered evidence in the literature, reinforcing that satisfaction and the repatronage intention can be increased. Additionally, the results highlight the complementary role of the mobile device in in-store purchases, assisting in decision making. The originality of the study relies on the inclusion of the effects of mobile devices and the verification of these effects on customer satisfaction, explaining how mobile devices influence the in-store shopping experience, contributes to advancing theoretical knowledge on this topic and provides valuable insights for retailers.